Chiral information harvesting in helical poly(acetylene) derivatives using oligo(p-phenyleneethynylene)s as spacers. Issue 27 (29th June 2020) - Fernández, Zulema; Fernández, Berta; Quiñoá, Emilio; Riguera, Ricardo; Freire, Félix
Abstract : A chiral harvesting transmission mechanism is described in poly(acetylene)s bearing oligo( p -phenyleneethynylene)s (OPEs) used as rigid achiral spacers and derivatized with chiral pendant groups. Abstract : A chiral harvesting transmission mechanism is described in poly(acetylene)s bearing oligo( p -phenyleneethynylene)s (OPEs) used as rigid achiral spacers and derivatized with chiral pendant groups. The chiral moieties induce a positive or negative tilting degree in the stacking of OPE units along the polymer structure, which is further harvested by the polyene backbone adopting either a P or M helix.